Successful exclusive breastfeeding through ‘‘Kiper Si Gizi’’ to mothers since pregnancy - Hapsari, Sri; Noor SU, Yuliana; Purwanti, Dwi (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
ABSTRACTBackground: One of the important intakes given to infants is exclusive breastfeeding. Training mothers to be ready to breastfeed is done since they are pregnant. Website media makes it easier for mothers to access information online.Objective: To increase the success of exclusive breastfeeding through website-based nutrition education ‘Kiper Si Gizi’ (Kelompok Ibu Peduli ASI dan Gizi) for mothers since pregnancy.Methods: Quasi-experimental design with two-group pre- and post-test control group design and two-group post-test only control group design. The subjects were 30 pregnant women in trimester 3 at Puskesmas Dempet, Demak Regency, who received ‘Kiper Si Gizi’ education and 30 mothers at Puskesmas Wedung II, Demak Regency, who received Maternal and Child Health (MCH) book education. Statistical tests to determine differences in knowledge, attitudes and differences in breastfeeding practices used Independent sample T-test. Chi Square test to test the difference in exclusive breastfeeding success between the two groups. Results: The average change in knowledge of pregnant women after being given education using website media (25%) was more effective (p=0.007) than using MCH book media (16.33%). The average change in the attitude of pregnant women after being given education using website media (Δ=10.20) is more effective (p=0.025) than using MCH book media (Δ=7.4). The breastfeeding practice score of mothers after being educated using the website media (score=9.6) was more effective (p= 0.017) than using the MCH book media (score=8.5). Mothers who breastfeed exclusively in the website group are more (83.3%) and different (p= 0.001) than the MCH book group (40.7%).Conclusion: Education with ‘Kiper Si Gizi’ can improve knowledge, attitudes, breastfeeding practices and more exclusive breastfeeding better than the MCH book.Keywords : Exclusive breastfeeding; MCH book; ‘Kiper Si Gizi’; website